An ecological study of freshwater ecosystem and its colligation to Odonates assemblages in Ipogun, Southwest Nigeria - Adu, Babasola (2023)
Odonata (dragonfly and damselfly) are particularly good indicators of freshwater ecosystem health. The constant disturbance of freshwater habitats can result in the reduction of Odonata species diversity. Changes in Odonata biodiversity are influenced by several human activities, such as agriculture, urbanization, input of pollutants in water and construction. This study was carried out to assess the abundance and diversity of Odonata, evaluate the physicochemical characteristics of water, and compare the community structure of Odonata at three selected sites along River Aponmu in Ipogun. Adult odonates were sampled and identified for 11 months using a sweep net, water samples were collected and some parameters were determined during the study period....